Flaxseed extract and its effect on wnt signaling pathway in the osteogenic differentiation potential of stem cells from human exfoliated deciduous teeth (shed). - Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Lestari, Widya; Arief Ichwan, Solachuddin Jauhari; Darnis, Deny Susanti; Nordin, Nur Sazwi; Thirumulu Ponnuraj, Kannan; Ahmad, Azlina (2020)
Flaxseed (Linum usitatissimum) contains beneficial compounds which have been recognized for its health benefits. Flaxseed extract promotes bone health especially in estrogen deficient individuals and possibly able to induce bone regeneration process. The WNT signaling plays critical role during developmental process and involved in regulating bone formation. Interestingly, WNT signaling is an important regulatory pathway in lineage differentiation of mesenchymal stem cells (MSC) including osteogenic differentiation through canonical WNT pathway. Stem cell from human exfoliated deciduous teeth (SHED) is an alternative source of MSC in tissue regeneration and tissue engineering because of their potential to differentiate into multiple cell lineages including osteoblast. Although flaxseed extract has been shown to affect bone formation process, its effect in inducing dental pulp-related stem cell into osteoblast lineage has not been reported. Additionally, its effect on WNT signaling mechanism involved during the osteogenic differentiation of SHED warrants further investigation. The aim of the project was to study the effects of flaxseed extract on osteogenic differentiation potential of SHED and its effect on WNT signaling related-molecules expression during osteoblast differentiation process of SHED. Flaxseed was extracted using ethanol as the solvent and subjected for GC-MS analysis. Cell viability test of flaxseed extract on SHED were performed accordingly. Alizarin Red-S staining and alkaline phosphatase (ALP) activity were performed on SHED cultured in either complete growth media or osteoblast induction media (OIM) with or without flaxseed extract. Total RNA was extracted from SHED at specific days and subjected to cDNA synthesis prior to reverse transcriptase-PCR (RT-PCR) analysis utilizing specific primers for stem cell markers (NANOG and OCT4) and osteoblast markers (OSX, DMP1 and OCN). GAPDH was used as internal positive control. To determine the effect of flaxseed extract on the expression of WNT signaling pathway-related molecules (WNT5a, DKK1 and β-CATENIN), total RNA from SHED cultured in osteoblast induction media with/without flaxseed was also extracted and subjected for RT-PCR. The expression of these genes were also analysed to determine the effects of flaxseed extract, on WNT signaling pathway-related molecules when treated in the presence of exogenous DKK1; a WNT signaling inhibitor. Overall, flaxseed at concentration up to 4 mg/ml retained SHED proliferation activity while maintaining cell viability, morphology and the expression of stem cell markers. The positive effect of flaxseed on maintaining the proliferation of SHED might be due to the presence of the active compounds in flaxseed. SHED demonstrated no morphological changes and reduction in ALP and Alizarain red-S staining and reduced the expression of OSX, DIMP1 and OCN when cultured in OIM treated with flaxseed. Addition of flaxseed into SHED cultured in OIM; in the presence of DKK1 inhibitor, affected the expression of WNT signaling-related molecules (β-catenin, DKK1 and WNT5A). Interestingly, the gene expression analysis revealed that addition of flaxseed to the culture treated with rhDKK1 significantly increased the expression of β-catenin, and DKK1 genes as well as WNT5A, compared to the expression observed in untreated SHED (without flaxseed extract but with rhDKK1 treatment only). The addition of flaxseed appears to re-enhance the expression of WNT associated molecules; thus we proposed that in the presence of rhDKK1 that may have initially blocked the WNT pathway, treatment with flaxseed extract could counteracted the DKK1 inhibitor action, thus re-induced the gene expression of WNT associated molecules. Flaxseed extract might block the effect of DKK1 inhibitor thus proposing flaxseed to act as natural-based medication for disease of bone development related to abnormality of WNT signaling pathway.